MENELUSURI RUANG EKONOMI KOTA SEBAGAI GENIUS LOCI DI KAWASAN PECINAN JAKARTA BARAT - Andiani, Nathania; Ekomadyo, Agus Suharjono (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2021)
Abstract: The Chinatown is part of the historical development of a city. Therefore, the Chinatown forms space and place of a city. The Chinatown has many characters and characteristics forms a place that has a meaning of the place. Glodok’s Chinatown is identical to the area of Chinese ethnicity and has a strong character in the economic sector. The purpose of this study is to explore the economic space of the city by looking at visual expressions, spaces form, and character of the created areas. This study will analysis using a phenomenological approach architecture